MAPPING MEANING: A PRAGMA-DISCOURSE STUDY OF STRUCTURAL METAPHORS AND IDEOLOGICAL REPRESENTATION IN AMERICANAH AND PURPLE HIBISCUS (Contemporary Journal of Social Science Review, 2025)
This study analyzed the structural metaphors and the ideologies they represent in the novels Americanah and Purple Hibiscus of Chimamanda Ngozie Adichie using a pragma-discourse analysis, an interdisciplinary approach combining elements from both Pragmatics and Discourse Analysis. The study used qualitative analysis, drawing on the theory of conceptual metaphor presented by George Lakoff and Mark Johnson to unveil the intricate layers of conceptual metaphors and ideologies used in the dialogues of the selected novels. The Pragglejaz Metaphor Identification Procedure (2007) was used to recognize the metaphorical language expressions. Data collected from both the novels was analyzed in two phases, in the first phase the conceptual/cognitive metaphor analysis was applied that follows three steps of analysis; identification, interpretation, and explanation.  Only conceptual metaphors that met the requirements were identified. In the second phase, the identified metaphors were rigorously evaluated to determine that the metaphors were employed figuratively as a choice and not as a standard. The study explained the conceptual domains that are source and target domains into a tabulated form by deducing their in-depth meaning that underpins the language of the characters in the selected novels. The analysis of conceptual metaphors was based on conceptual /critical metaphor analysis in the field of pragmatic discourse. The major findings were related to structural metaphor and its sub-category money metaphor which was identified in the dialogues of the characters in the mentioned two novels. Finally, their source and target domains were mapped onto each other for getting into the ideological underpinnings of the characters.